Partial restoration of normal intestinal microbiota in morbidly obese women six months after bariatric surgery - Koffert J; Lahti L; Nylund L; Salminen S; Hannukainen JC; Salminen P; de Vos WM; Nuutila P (United Kingdom, 2022)
We studied the impact of bariatric surgery on the intestinal microbiota of morbidly obese study subjects. A total of 13 morbidly obese women (five of which had type 2 diabetes) and 14 healthy age- and gender-matched controls were recruited and the microbiota composition of fecal samples were determined by using a phylogenetic microarray. Sampling of the patients took place just one month before and 6 months after the operation. Within six months after bariatric surgery, the obese subjects had lost on average a quarter of their weight whereas four of the five of the diabetic subjects were in remission. Bariatric surgery was associated with an increased microbial community richness and Bacteroidetes/Firmicutes ratio. In addition, we observed an increased relative abundance of facultative anaerobes, such as Streptococcus spp., and a reduction in specific butyrate-producing Firmicutes. The observed postoperative alterations in intestinal microbiota reflect adaptation to the changing conditions in the gastrointestinal tract, such as energy restriction and the inability to process fiber-rich foods after bariatric surgery.